Uma experiência de ensino crítico com alunas/os iniciantes de inglês: foco em gênero e sexualidade - FERNANDES, Luciana Rezende (2012)
This study is characterized as a critical case study of qualitative nature. It consists in the development of several critical activities, focusing on gender and sexuality issues, in two groups of English for beginners at the Centro de Línguas of Universidade Federal de Goiás in 2010. The activities dealt with situations experienced by women and by the female students themselves, when discussing women‟s double shift; different forms of experiencing gender, when dealing with the Saturday routine of two transvestites; and alternative family arrangements, other than those enforced by the hegemonic standard, when presenting families of homosexual couples. The intention was to observe the reactions of the students to the critical issues, the possibilities and challenges of carrying out critical teaching for beginners, and my attitude as a teacher researcher when addressing these critical issues in the classroom. The theoretical background is centered in the following topics and authors: Critical Applied Linguistics (COX; ASSIS-PETERSON, 1999; FERREIRA, 2006; MOITA LOPES, 1999, 2006; PENNYCOOK, 1998, 2001, 2006); gender and sexuality (LOURO, 2007, 2010; MOITA LOPES, 2002); critical teachers (GIROUX, 1997; SCHÖN, 1983, 2000; SMYTH, 1991; VAN MANEN, 1995, 2007, 2008). The students‟ reactions to the critical issues were varied, among which we can point out comments, jokes, gestures and expressions of embarrassment, detachment from the subject, silence, refusal in doing the activity, omission of the issue, denial, and active participation in carrying out the oral or written activity. The feasibility and the relevance of carrying out critical teaching for beginners were demonstrated by the reflections performed by the students in written and oral activities, indicating the development of a more pluralistic approach to gender and of their linguistic competence. As for my attitude when addressing critical issues, I believe I have achieved reflection on action (SCHÖN, 1983, 2000; VAN MANEN, 1995, 2008) by assuming a political attitude in the choice of the issues and in the planning of the critical activities to be carried out in the classroom. However, I had difficulty in performing reflection in action (SCHÖN, 1983, 2000; VAN MANEN, 1995, 2008) since I had a tendency not to react to critical events that occurred in the classroom. Thereby, I think I have reached the fourth moment of Smyth‟s critical reflection (1991) since I reconstructed my practice, that is, when shifting the focus of my lessons towards critical activities and issues, but I was not able to reconstruct my action with regard to the attitude of not reacting to critical events.